Vertical Load and Settlement at the Foot of Steel Rib with the Support of Feet-Lock Pipe in Soft Ground Tunnel - Lijun Chen; Jianxun Chen; Yanbin Luo; Yao Li; Taotao Hu (Advances in Civil Engineering)
In soft ground tunnels, feet-lock pipes have been widely used to decrease the concentration of load and settlement at the foot of steel ribs. This paper presents an analytical method to predict the vertical load and settlement at the foot of steel ribs with the support of the feet-lock pipe. First, the mechanical model of a steel rib and feet-lock pipe combined structure involving the ground reaction at the foot was proposed. In this model, the deformation compatibility among the steel rib, the feet-lock pipe, and the ground at the tunnel foot were considered, and an elastic foundation beam model with double parameter for the feet-lock pipe was proposed. Then, based on the proposed mechanical model, the analytical equations for predicting the vertical load and settlement at the foot of the steel rib were derived using structural analysis and beam theory on elastic foundation. The predicted vertical loads and settlements were validated by comparing with the results of field measurements and the Winkler foundation beam model for the feet-lock pipe, and the results show that the feet-lock pipe can effectively reduce the load acting on the ground, where the steel rib was installed, and finally improve the stability of the tunnel structure.